Counting the Invisible Working Hands in India (Global Journal of Human-Social Science, 2021)
This paper enquires into the problem faced by migrant labors in the informal sector in India. It argues for the registration and tracking of migrants, particularly interstate migrants, as they constitute a significant proportion of the labour force. The mobility of labor is the natural mechanism for infusing inclusive and faster growth across the globe, and tracking the poor migrants would lead to investment in human and social capital, paving the way for integrating poverty alleviation policies and development strategies for overall better outcomes.
Keywords: poverty; labour economic; human capital